Steroid Pulse Therapy for Severe Central Nervous System Involvement in Shiga Toxin-Producing Escherichia coli-Related Hemolytic Uremic Syndrome - Chiara Rosazza; Alberto M Cappellari; Cristiano Gandini; Elisa Scola; Gianluigi Ardissino (Case Reports in Pediatrics)
We report on the case of a 7-year-old boy with Shiga toxin-producing Escherichia coli-related hemolytic uremic syndrome (STEC-HUS), initially presenting with abdominal pain as the only clinical feature and thus requiring differential diagnosis with a surgical emergency. Diagnosis of STEC-HUS was made with the appearance of bloody diarrhea and renal function impairment, and the clinical picture rapidly progressed to multiorgan failure. Relatively late and severe central nervous system (CNS) involvement was present, characterized by subacute encephalitis progressing to coma, which became apparent when the acute phase of thrombotic microangiopathy was resolving. Therefore, neurologic manifestations were thought to be related to reperfusion damage to the CNS and high-dose IV steroid pulse therapy was empirically administered. Following this therapeutic scheme, neurologic involvement resolved with no sequelae. This case offers several points of discussion on the clinical presentation and the diagnostic approach to STEC-HUS, on the related neurologic complications, and on a novel approach to their management.